Pre-Purchase Behavior of Consumer with Reference to Car in Nepal - Neupane, Surendra (Journal of Advanced Academic Research, 2017)
The purpose of this study is to investigate the pre purchase behavior of car consumers in Nepal. In order to accomplish the objectives of the study, a sample of 400 consumers were taken by using simple random sampling technique. The data was collected by means of a questionnaire. Both primary and secondary data were explored and analyzed through descriptive analysis. From the analysis, it was concluded that the respondents owned a car as a necessity item, they had a cause need to manage money for time gap between car purchase and need assessment, friends and relatives were the primary source of information. Consumers paying more attention to relevant factors before deciding the brand such as pre purchase search, reference group and self opinion. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 138-146